Effectiveness of Nephron Sparing Surgery and Radical Nephrectomy in the Management of Unilateral Wilms Tumor: A Meta-Analysis - Chen, Hongkun; Yang, Shuqing; Qian, Cheng (Frontiers in Oncology, 2020)
Background: Unilateral Wilms tumour is the most common renal malignancy in the paediatric population. Although the onset of surgical intervention like radical nephrectomy has substantially reduced the mortality rate, recent evidence has raised concerns regarding several post-operative complications associated with this procedure. Nephron sparing surgery has been reported to avoid such post-operative complications that too with a high technical success rate. However, no attempt to date has been made to synthesize the evidence comparing the efficacy of radical nephrectomy and nephron sparing surgery for managing unilateral Wilms tumour. Methods and results: To meta-statistically compare the efficiency of radical nephrectomy with nephron sparing surgery for managing unilateral Wilms tumour a systematic identification of literature was performed according to PRISMA guidelines on 4 academic databases: MEDLINE, Scopus, EMBASE & CENTRAL. A meta-analysis comparing renal function (estimated glomerular filtration rate), survival rate and rate of relapse was performed to compare the efficacy of radical nephrectomy and nephron sparing surgery. Out of 1,283 records, 20 articles including 5,246 children (mean age: 4.3 ± 3.0 years) were included in this review. Radical nephrectomy was performed on 11 of the included studies, whereas nephron sparing surgery was performed on five studies. Two studies compared the efficacy of both interventions. The meta-analysis reveals the beneficial effects of nephron sparing surgery (Hedge’s g: 0.76) as compared to radical nephrectomy (-0.16) for the estimated glomerular filtration rate for children with unilateral Wilms tumour. Moreover, higher survivability (0.59) and lesser occurrence of relapse were (-1.0) also reported for cases operated with nephron sparing surgery. Conclusion: The current meta-analysis recommends the use of nephron sparing surgery for unilateral Wilms tumour. The procedure accounts for higher survivability, postoperative renal function and lesser incidence of relapse as compared to radical nephrectomy.